ANALYSIS OF PROBLEM SOLVING CYCLE (PSC) IN ACCOUNTING AND FINANCIAL REPORTING IN REGIONAL GENERAL SERVICES AGENCY - Widyajasita, Aulia (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Public Service Agency Hospital is a general government agency whose activities are also selling goods or services. Financial statements are a tool for making rational decisions in sound business practices. The financial reporting process for Hospital BLU has been regulated in the Minister of Finance Regulation Number 76/PMK.05/2008 concerning Guidelines for Accounting and Financial Reporting for Public Service Agencies and the Decree of the Minister of Health of the Republic of Indonesia Number 1981/MENKES/SK/XII/2010 concerning Accounting Guidelines for Service Agencies. General (BLU) Hospital. The method used is a literature study of journals on Financial Statements in several BLUDs, as many as 10 journals, and the stages of Situation Analysis, Problem Identification, Problem Priority Determination, Problem Alternative Development, and Plan of Action are carried out. The results of the PSC analysis obtained that the priority problems were